IMPLEMENTASI SISTEM PENDIDIKAN NASIONAL DI PONDOK PESANTREN DARUL QURAN BANDUNG - Aisah, Heti; Nurwadjah Ahmad; Andewi Suhartini (re-JIEM (Research Journal of Islamic Education Management), 2020)
Pesantren is an Islamic religious education institution that has Kyai, students, boarding schools and mosques. Pesantren education institutions have made a major contribution in their role in advancing the world of education in Indonesia. This article aims to examine the role of the Darul Quran Islamic boarding school in implementing the national education system. This research uses descriptive qualitative research methods, with data collection techniques through interviews, documentation study and observation. The results showed that the Darul Quran Islamic boarding school in Bandung was able to demonstrate its role in the national education system, through the Daqu method, and the Daili Activity which led the students to have attitudes, knowledge and skills to meet 21st century competencies.